2013
DOI: 10.1038/jid.2013.78
|View full text |Cite
|
Sign up to set email alerts
|

Which Antipsoriatic Drug Has the Fastest Onset of Action?—Systematic Review on the Rapidity of the Onset of Action

Abstract: The time necessary for a treatment to become effective is crucial for patients and physicians but has been largely neglected in the reporting and comparison of clinical trials in dermatology. The aim of this systematic review is to determine the time until the onset of action (TOA) of systemic agents approved for moderate-to-severe psoriasis. Primary outcome is the TOA defined as the weighted mean time until 25% of the patients achieved a psoriasis area and severity index (PASI) 75 response. Among the biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 64 publications
5
51
0
3
Order By: Relevance
“…Similar to the findings of previous studies, 1,2 we demonstrate faster and more complete clinical disease responses among adalimumab-treated than methotrexate-treated patients. We show that methotrexate responders compared with methotrexate nonresponders experience significant down-regulation of mRNAs in the T H 1-, T H 17-, and T H 22-related signaling pathways and normalization of psoriasis transcriptome genes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to the findings of previous studies, 1,2 we demonstrate faster and more complete clinical disease responses among adalimumab-treated than methotrexate-treated patients. We show that methotrexate responders compared with methotrexate nonresponders experience significant down-regulation of mRNAs in the T H 1-, T H 17-, and T H 22-related signaling pathways and normalization of psoriasis transcriptome genes.…”
Section: Discussionsupporting
confidence: 90%
“…Despite methotrexate’s significantly lower cost, current evidence suggests that biological agents are safe, have a faster onset of clinical response, and demonstrate an overall higher efficacy than methotrexate. 1,2 However, no known studies have evaluated methotrexate’s effects on pathway regulation in psoriasis or compared the changes induced by methotrexate and biological agents at the genomic, immunohistochemical, and mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infliximab is the most efficacious treatment option for induction treatment of psoriasis, and has also been shown to have the fastest onset of action of all of the treatments available. 63 The evidence base indicating efficacy of the biologics infliximab, adalimumab, ustekinumab and etanercept is much stronger than the evidence for efficacy of conventional treatment options for moderate-to-severe psoriasis. Trials investigating biologics for psoriasis were much larger, on average had a longer duration, and had lower risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…Although the currently available data allow only a limited assessment, a recent systematic review showed that monoclonal antibodies (infliximab, ustekinumab and adalimumab, in decreasing order) have the fastest onset of action (52). Data also showed a significant mean PASI improvement by week 12 in patients receiving etanercept 50 mg twice-weekly dose (53).…”
Section: Adherencementioning
confidence: 99%